KUALITAS KIMIA SUSU SEGAR KAMBING SAPERA PADA WAKTU PEMERAHAN YANG BERBEDA - Agung Dwi Prasetiyo; Danang Biyatmoko; Habibah Habibah (www.ulm.ac.id, 2023)
This study anime purpose of this study was to determine the differences in milking time on thechemical quality of Sapera goat fresh milk. Testing the chemical quality of milk was carried outat the Livestock Production Laboratory, Department of Animal Husbandry, Faculty ofAgriculture, University of Lambung Mangkurat, while the milk samples were taken from CV. Aseries of Ark Awards, Mandiangin, Banjar Regency, South Kalimantan. This study used acompletely randomized design (CRD) with 3 treatments and 6 replications where each replicationconsisted of 1 goat. The research treatment was the difference in milking time, namely P1 =Milking time at 08.00 WITA; P2 = Milking time at 12.00 WITA; P3 = Milking time at 16.00WITA. Based on the results of the study the difference in milking time did not affect the qualityof Sapera goat's milk, both protein content, fat content, BKTL, and lactose levels. The threetreatments produced milk with nutritional quality according to SNI 3141.1 2011 standards.